Animal models of alcohol and drug dependence - Planeta, Cleopatra da Silva [UNESP] (Associação Brasileira de Psiquiatria - ABP, 2013)
Drug addiction has serious health and social consequences. In the last 50 years, a wide range of techniques have been developed to model specific aspects of drug-taking behaviors and have greatly contributed to the understanding of the neurobiological basis of drug abuse and addiction. In the last two decades, new models have been proposed in an attempt to capture the more genuine aspects of addiction-like behaviors in laboratory animals. The goal of the present review is to provide an overview of the preclinical procedures used to study drug abuse and dependence and describe recent progress that has been made in studying more specific aspects of addictive behavior in animals.
Keywords: Animal model; dependence; addiction; drugs of abuse